Efeitos de baixas doses de cloprostenol via intramuscular ou submucosavulvar na indução do estro e taxas de prenhez em vacas Nelore - Mungai Chacur, Marcelo George; Ferreira Aurelio, Paulo Tiago; Scalon Junior, Orivaldo; Inague, Leandro; Scalon, Luis Fernando; Kronka, Sergio do Nascimento [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
The present study aims to compare the effects of lower doses of cloprostenol intramuscular (IM) or into vulvar submucosa (IVS) on estrus induction and pregnancy rate in Nelore cows. A total of 100 cycling Nelore cows with body condition score (BCS 3.5) 1 to 5 scale (Radostitis; Blood, 1986) and 170 +/- 11 days postpartum. Females were randomly divided in 5 groups (N=20) G1 to G5 and treated with cloprostenol (Ciosin (R)) on day 0 (D0) and on day 11 (D11) if not detected in estrus. Cows were injected with 500 mu g IM (G1), 250 mu g IM (G2), 125 mu g IM (G3), 250 mu g IVS (G4) and 125 mu g IVS (G5). Estrus was observed twice a day and the females artificially inseminated 12 hours after heat detection. There was no statistical difference (P>0.80) between groups in the estrus induction (first injection to estrus interval): 16/20-96.00 hours (G1), 13/20-90.42 hours (G2), 10/20-84.45 hours (G3), 15/20-87.86 hours (G4), 12/20-81.25 hours (G5) and second injection (P>0.10): 4/20-67.50 hours (G1), 7/20-85.50 hours (G2), 10/20-57.00 hours (G3), 5/20-70.60 hours (G4), 8/20-60.00 hours (G5). There was no statistical difference (0.65(ns)) between groups in the pregnancy rates: 40% (G1), 45% (G2), 50% (G3), 40% (G4), 40% (G5). The results demonstrate that the treatments with lower doses of cloprostenol intramuscular or into vulvar submucosa may be used to induce heat with similar pregnancy rates in cycling Nelore cows with good body condition.
Effects of lower doses of cloprostenol intramuscular or into vulvar submucosa on estrus induction and pregnancy rates in Nelore cows
Keywords: Zebu cows; Bos taurus indicus; prostaglandin; micro doses; artificial insemination